Відповідь:
19x-11y+12=0
Покрокове пояснення:Simplifying
19x + -11y + 12 = 0
Reorder the terms:
12 + 19x + -11y = 0
Solving
12 + 19x + -11y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-12' to each side of the equation.
12 + 19x + -12 + -11y = 0 + -12
Reorder the terms:
12 + -12 + 19x + -11y = 0 + -12
Combine like terms: 12 + -12 = 0
0 + 19x + -11y = 0 + -12
19x + -11y = 0 + -12
Combine like terms: 0 + -12 = -12
19x + -11y = -12
Add '11y' to each side of the equation.
19x + -11y + 11y = -12 + 11y
Combine like terms: -11y + 11y = 0
19x + 0 = -12 + 11y
19x = -12 + 11y
Divide each side by '19'.
x = -0.6315789474 + 0.5789473684y
Simplifying
x = -0.6315789474 + 0.5789473684y
Пошаговое объяснение:
1) 2 1/6 :(8 3/4-5 1/2)=2/3
8 3/4-5 1/2=8 3/4-5 2/4=3 1/4
2 1/6:3 1/4=13/6*4/13=2/3
2)3 17/20:(3 2/5+1 11/15) =3/4
3 2/5+1 11/15=3 6/15+ 1 11/15=4 17/15=
5 2/15
3 17/20:5 2/15=77/20*15/77=3/4
3) (4 3/5-2 1/5):1 1/10 =2 2/11
4 3/5-2 1/5=2 2/5
2 2/5:1 1/10=12/5*10/11=24/11=2 2/11
4)(1 7/10+4/5):1 7/8=1 1/3
1 7/10+4/5=1 7/10+8/10=1 15/10=2 1/2
2 1/2:1 7/8=5/2*8/15=4/3=1 1/3
5) 3 1/8:15/16-1/4
3 1/8:15/16=25/8*16/15=10/3=3 1/3
3 1/3-1/4=3 4/12-3/12=3 1/12
6)1 9/35:(1 1/5+2/3) =33/49
1 1/5+2/3=1 3/15+10/15=1 13/15
1 9/35:1 13/15=44/35*15/28=33/49
7) (11 5/8+7 1/6):3 5/12 =18 19/24
11 5/8+7 1/6=11 15/24+7 4/24=5 1\2
18 19\24:3 5\12=451\24*12\41=11\2=5 1\2
8) (8 7/12-2 5/8):2 1/6=2 3/4
8 7/12-2 5/8=8 14/24-2 15/24=5 23/24
5 23/24:2 1/6=143/24*6/13=11/4=2 3/4